Undercarboxylated Osteocalcin and Its Associations With Bone Mineral Density, Bone Turnover Markers, and Prevalence of Osteopenia and Osteoporosis in Chinese Population: A Cross-Sectional Study - Xu, Yang; Shen, Li; Liu, Lianyong; Zhang, Zhenlin; Hu, Weiwei (Frontiers in Endocrinology, 2022)
Objective: To obtain the profile of serum undercarboxylated osteocalcin (ucOC) level according to gender and age and explore its associations with bone mineral density (BMD), bone metabolism markers and prevalence of osteopenia and osteoporosis in Chinese population. Methods: This is a cross-sectional study with 900 subjects including 431 men and 469 women enrolled. Clinical information was collected, BMD of the lumbar spine (L1-4), left femoral neck and total hip were scanned, biochemical markers including hepatic and renal function, serum calcium, serum phosphorus, procollagen type 1 N-propeptide (P1NP), β-CrossLaps kit for b-CrossLaps of type I collagen containing cross-linked C-telopeptide (β-CTX), intact parathyroid hormone (PTH), 25-hydroxyvitamin D (25OHD) and ucOC were measured. Results: We found the median ucOC level was higher in men than women after adjusting for age, BMI and creatinine (Cr) [men: 2.6 ng/mL, women: 1.6 ng/mL; p<0.001]. The profile according to age showed that ucOC levels reached the lowest at the age of 40-49 yr in both men (2.62 ng/mL) and women (1.68 ng/mL), and before 49 yr, they decreased with age, then over 50 yr, they quickly increased. Furthermore, we found a higher ucOC level was correlated with lower BMD at lumbar spine (men: r=-0.142, p=0.005; women: r=-0.327, p<0.001), femoral neck (men: r=-0.111, p=0.027; women: r=-0.264, p<0.001) and total hip (men: r=-0.121, p=0.016; women: r=-0.213, p<0.001), and a higher P1NP (men: r=0.321, p<0.001; women: r=0.247, p<0.001) and β-CTX (men: r=0.183, p<0.001; women: r=0.355, p<0.001) level in both men and women. After adjusting for age, BMI and Cr, we also demonstrated that a 1-SD increase in ucOC was associated with an odds ratio (OR) of 1.65 and 1.73 for having osteopenia or osteoporosis in men and women, respectively (men: 95%CI=1.27-2.13, p<0.001; women: 95%CI=1.22-2.45, p=0.002). Conclusions: Our study first revealed the serum ucOC profile according to gender and age in Chinese population, and demonstrated that higher ucOC levels were associated with lower BMD at all sites, higher P1NP and β-CTX levels, and the higher risk of having osteopenia or osteoporosis in both men and women. Our findings may provide a clue to elucidate the function of ucOC in bone metabolism.